Play Thraphy on Fine Motor Skills of Pupils with Dysgraphia in Ikere Ekiti Local Government Area of Ekiti State - Ariyo, Ojo (TECHNOVATE: Journal of Information Technology and Strategic Innovation Management, 2024)
Dysgraphia is a specific learning disability affecting pupils' writing abilities, often leading to incomplete notes, poor handwriting, and low academic performance. This study examines the effect of play therapy on fine motor skills in pupils with dysgraphia in Ikere Ekiti Local Government Area, considering the roles of gender and self-esteem. Using a pretest-posttest control group quasi-experimental design, data were collected from male participants (average age 10±15 years) over six weeks, with instruments such as the Dysgraphia Screening Test, Writing Assessment, Self-Esteem Scale, and Weschler Intelligence Scale. Analysis using ANCOVA revealed a significant main effect of treatment on fine motor skills (f(1,59) = 158.705; p<0.05), but no significant effects of gender, self-esteem, or their interactions with the treatment. Based on the findings, the study recommends play therapy as an effective intervention for improving fine motor skills in pupils with dysgraphia